Sintomas ansiosos entre estudantes de uma universidade na fronteira franco brasileiro - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Introduction: Anxiety is considered a sign of precaution, determined by the presence of an internal conflict, whose function is to warn about an imminent risk to act carefully against the threat. Objectives: To trace the sociodemographic profile of students and to identify the prevalence of anxiety symptoms in students from a university in the franc-Brazilian frontier. Methods: This was a cross-sectional study developed at the Federal University of Amapá (UNIFAP), located on BR-156, in the municipality of Oiapoque, Amapá, during the school term and classes of each in order to facilitate the approach. The investigation followed all proceedings necessary to ethical researches involving human beings, being approved with CAEE: 04145218.7.0000.000. Data collection used primarily a self-administered questionnaire developed by the researcher, structured with closed questions, contemplating the variables and aspects related to the Beck Anxiety Inventory (BAI) Results: Most students that participated in the research were young adults and 82.4% were between 20 and 40 years, with predominance of female 58.6%, 51.9% single, 39.9% reported being evangelicals, 59.7% perform payed and curricular activities concomitantly. The evidence shows that the degrees of anxiety vary as follows: 156 (67.2%) with minimum anxiety, 36 (15.5%) with mild anxiety, 30 (12.9%) moderate anxiety and 10 (4.3%) severe anxiety. Conclusion: These data demonstrate a low prevalence of symptoms of anxiety among the students from the Federal University of Amapá, but the care with the students is essential, with a focus on self-care and self-knowledge. The survey should be deepened, covering the various stages of the course, in addition to health promotion and focusing on mental health
Keywords: Saúde na fronteira; Ansiedade; Estudante universitário; Oiapoque (AP); CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA